Dealing with Pheochromocytoma during the First Trimester of Pregnancy - Konstantinos Kiroplastis; Apostolos Kambaroudis; Apostolos Andronikou; Andromachi Reklou; Dimitris Kokkonis; Panagiotis Petras; Apostolos Mamopoulos; Eudokia Anagnostara; Charalampos Spyridis (Hindawi Limited, 2015)
Purpose. Pheochromocytoma in association with pregnancy is a very rare, without specific symptoms, life-threatening condition, increasing both maternal and fetal mortality up to 50%. The present paper illustrates the case of a pregnant woman, diagnosed with pheochromocytoma, aiming to demonstrate and discuss the difficulties that arouse during the diagnosis and the problems concerning the treatment. Patient. A 34-year-old woman, in the 9th week of pregnancy, complained for headache, sweating, and a feeling of heavy weight on the right renal area. A tumor of 10 cm diameter at the site of the right adrenal was found. Twenty-four-hour urine catecholamine and VMA excretion levels were well raised. Results. Multidisciplinary approach treated the patient conservatively. Surgical resection of the tumor was performed after the 14th week of pregnancy at the completion of organogenesis. Neither postoperative complications occurred nor hypertension relapse was recorded. The fetus was delivered without complications at the 36th week. Conclusions. There are no consensus and guidelines for treating pheochromocytoma during pregnancy, especially when it is diagnosed in the first trimester. The week of pregnancy and a multidisciplinary approach will determine whether the pregnancy should be continued or not, as well as the time and the approach of surgical treatment.